ANÁLISE E INTERPRETAÇÃO DE MATERIAIS CERÂMICOS DO SÍTIO ARQUEOLÓGICO ROSÁRIO, GUAÍRA - SÃO PAULO - Fernando Henrique Ferreira de Oliveira; Neide Barrocá Faccio; Juliana Aparecida Rocha Luz (Universidade do Oeste Paulista, 2013)
The objective of this paper is to discuss the results of the curatorship and analysis of ceramics from Rosário Archaeological Site, situated in Guaíra, state of São Paulo. We sought to relate the elements of archaeological culture with the physical aspects of the environment present in such archeological landscape. The research aimed to understand the relation between the elements of the archaeological culture and the landscape, unit of study comprehended through the dialectical relation between natural elements and humans. Thus, analyzing the ceramics through operational chain and study of the landscape, we add contributions to the knowledge of the past occupations in the North of São Paulo State.